GPS constraints on deformation in northern Central America from 1999 to 2017, Part 1 – Time-dependent modelling of large regional earthquakes and their post-seismic effects. Issue 3 (23rd June 2018) - Ellis, A; DeMets, C; Briole, P; Cosenza, Beatriz; Flores, Omar; Graham, Shannon E; Guzmán-Speziale, Marco; Hernández, Douglas; Kostoglodov, Vladimir; LaFemina, Peter; Lord, Neal; Lasserre, Cécile; et al.
SUMMARY: We use continuous and campaign measurements from 215 GPS sites in northern Central America and southern Mexico to estimate coseismic and afterslip solutions for the 2009 M w = 7.3 Swan Islands fault strike-slip earthquake and the 2012 M w = 7.3 El Salvador and M w = 7.4 Guatemala thrust-faulting earthquakes on the Middle America trench. Our simultaneous, time-dependent inversion of more than 350 000 daily GPS site positions gives the first jointly consistent estimates of the coseismic slips for all three earthquakes, their combined time-dependent post-seismic effects and secular station velocities corrected for both the coseismic and post-seismic deformation. Our geodetic slip solutions for all three earthquakes agree with previous estimates that were derived via static coseismic-offset modelling. Our time-dependent model, which attributes all transient post-seismic deformation to earthquake afterslip, fits nearly all of the continuous GPS site position time-series within their several-millimetre position noise. Afterslip moments for the three earthquakes range from 35 to 140 per cent of the geodetic coseismic moments, with the largest afterslip estimated for the 2012 El Salvador earthquake along the weakly coupled El Salvador trench segment. Forward modelling of viscoelastic deformation triggered by all three earthquakes for a range of assumed mantle and lower crustal viscosities suggests that it accounts for under 20 per cent of the observed post-seismic deformation and possibly under 10 per cent. Our results thus point to afterslip as the primary and perhaps dominant mode of post-seismic deformation for these three earthquakes. Forward modelling of post-seismic deformation associated with the larger M w = 7.6 September 2012 Costa Rica thrust earthquake suggests that afterslip, viscoelastic flow, or some combination thereof was responsible for a significant change in motion observed at a GPS site on San Andres Island in the Caribbean Sea more than 500 km from all four earthquakes. The measurable effects of the 2009 and 2012 earthquakes on the motions of GPS sites in nearly all of northern Central America underline the importance of time-dependent calibrations for transient, earthquake-related effects for studies of steady-state deformation processes.